Performance measurement system using balanced score card: a case study in Pusat Zakat Melaka, Malaysia / A'ieshah Abdullah Sani...[et.al] - Abdullah Sani, A'ieshah; Saidin, Amilia; Adanan, Siti Azrina; Bustamam, Khair Syakira (Center for Islamic Philantrophy & Social Finance (CIPSF), 2019)
The introduction of Balanced Score Card (BSC) as one of the management accounting tools to measure the performance of companies in both aspects of financial and non-financial positions has been predominantly used since 1992 and has resulted in positive energies for the profit-making companies. Hence, the extension of the BSC is also required to help the social business organisations in delivering their multiple bottom lines in the most effective ways and providing organisations a mechanism to track their performance holistically through both quantitative and qualitative information. The objective of this paper is to identify and evaluate the indicators used in the BSC as a performance measurement tool for the Islamic Philanthropy Institutions (IPI)s mainly in Pusat Zakat Melaka (PZM) under four main perspectives which are financial perspective, stakeholder's perspective, internal process perspective and learning and growth perspective in order to achieve the institute's vision and mission. The findings show that the indicators available for all of the perspectives can be measurable and consistent with the institute's mission and vision. The outcome of this study could provide a guideline in designing a proper measurement system that can be implemented by the other IPIs in Malaysia in order to maintain its sustainability and competitiveness in future.